Cultivos de anéis de traquéia para ensaios com o vírus da bronquite infecciosa das galinhas - Ericka de Oliveira Bicalho Epiphanio (1998)
The tracheal organ cultures (TOC) were prepared with tracheas from 19-day-old chicken embryos, The 1-2 mm thick rings were hand chopped and transfered to tubes with different medium cultures with five repetions of each for comparative evaluation and kept under continuous rotation using a roller and sored at 37° C. Medium RPMI 1640 added with HyQCCM proved superior in maintaining ciliary activity as compared to non-supplemented 199, or RPMI 1640 media. The rings with good (50%) and excellent (100%) ciliary activity, 24 or 48 hours aiier the preparation, were evaluated as regards sensibility to titration of a IBG and to the test of serum neutralisation. The use of TOC was evaluated for the titration of IBV strains M41, A5968 and H-120. The vaccine strains H-120 was carried out simultaneously and compared to the titration in embryonated hens eggs (EE) SPF. Results of titration of IBV in TOC, as compared to EE, were reproducible and represent na excellent alternative to titrating IBV field strains, due to the immediate viral replication without the need of` adaptation. Serum neutralisation (SN) was established using the M4l or A5968 IBV strains and the respective specific serum. Results were coherent to the literature and neutralisation of` known strains occurred only when serum and virus of a same serotype matched.Specific sera prepared against Brazilian iield strains were examined using M4l, A5968 and H-120 strains of` IBV. Sera to 208, 29/78 and PM2 neutralised M41 but not A5968, suggesting their specificity to be related to the Massachusetts serotype and not Connecticut. PM4 . ' specific serum did not neutralise any of the strains used, indicating its specificity to be neither Massachusetts nor Connecticut. H-120 vaccine strain was neutralised by sera of Massachusetts serotype, including serum specific to H·52 but not by serum of Connecticut serotype